Respuestas

2012-08-22T01:34:11+02:00

Resolución ejerciio 1:

(ctg^{2}x+1)*sen^{2}x=1\ si \recuedas\ que\ csc^{2}x=1+ctg^{2}x\ entonces:\\ csc^{2}x*sen^{2}x=1\\ \frac{1}{sen^{2}x}*sen^{2}x=1\ simplifico\\ 1=1

 

Resolución ejercicio2:

\frac{ctg^{2}x-cos^{2}x}{csc^{2}x-1}=cos^{2}x\ si recuerda \ que: csc^{2}x=1+ctg^{2}x\\ \frac{ctg^{2}x-cos^{2}x}{ctg^{2}x}=cos^{2}x\ distribuyo \ el \ denominador\\ \frac{ctg^{2}x}{ctg^{2}x}-\frac{cos^{2}x}{ctg^{2}x}=cos^{2}x\\ 1-\frac{cos^{2}x}{\frac{cos^{2}x}{sen^{2}x}}=cos^{2}x \ hago \ extremos \ y \ medios\\ 1-\frac{cos^{2}x*sen^{2}x}{cos^{2}x}=cos^{2}x\\ 1-sen^{2}x=cos^{2}x \ si \ recuerdas \ que\ sen^{2}x+cos^{2}x=1\\ cos^{2}x =cos^{2}x

 

AHORA AYUDAME TU MARCANDOLA COMO LA MEJOR RESPUESTA.. GRACIAS